Erratum: ROMAN KUCHTA, ALENA BURIANOVÁ, MILOSLAV JIRKŮ, ALAIN de CHAMBRIER, MIKULÁŠ OROS, JAN BRABEC & TOMÁŠ SCHOLZ (2012) Bothriocephalidean tapeworms (Cestoda) of freshwater fish in Africa, including erection of Kirstenella n. gen. and description of Tetracampos martinae n. sp.. Zootaxa, 3309, 1–35. - Kuchta, Roman; Burianová, Alena; Jirků, Miloslav; de Chambrier, Alain; Oros, Mikuláš; Brabec, Jan; Scholz, Tomáš (Zootaxa, 2012)
(Erratum)